Disinventing and reconstituting language for learning in school Science. (4th March 2019) - McKinney, Carolyn; Tyler, Robyn
Abstract: Language ideologies profoundly shape and constrain the use of language as a resource for learning in 'multilingual' or linguistically diverse classrooms. In this paper, we draw attention in particular to the ideology of languages as stable, boundaried objects and to the colonial invention of African languages. Against this backdrop, we analyse an example of pedagogical practice which was designed in response to a linguistic ethnography of Year 9 Science learning in a South African high school. The aim of this intervention is to move beyond the constraints of current language ideologies and to enable bilingual isiXhosa/English students to use a wide range of resources from their semiotic repertoires for learning Science. We will argue that debates about language of instruction in post-colonial contexts which pit one named language against another, misdirect our attention away from how the resources of language and other semiotic modes are or are not being used for learning in classroom discourse and learning materials. We aim to show how pedagogical translanguaging and trans-semiotising can be taken up as strategies of disinvention and reconstitution of 'language' for learning Science. (195)